The livestock revolution: a view on implications for Africa - Mwangi, David Miano; Omore, Amos O. (Cambridge University Press, 2004)
A rapid growth in per capita consumption of livestock products is occurring in developing countries (Delgado et al., 1999; FOASTAT 1983-2002). In the last two decades and until 2020, the increase in the consumption of meat and milk has been estimated to be much higher in developing countries compared to developed countries (Delgado et al. 1999). This increase in consumption and demand is fuelling an increase in production.